Primary health care nurses' mental health knowledge and attitudes towards patients and mental health care in a South African metropolitan municipality - Nanteza Gladys Kigozi-Male; James Christoffel Heunis; Michelle Catherine Engelbrecht (BMC, 2023)
Abstract Background In South Africa, there are on-going calls to integrate mental health services into existing primary health care (PHC) programmes such as Tuberculosis (TB). Successful service integration and quality service delivery partially depend on healthcare providers' mental health-related knowledge and attitudes. The aim of this study was to assess PHC nurses' mental health knowledge and attitudes towards mental health patients and mental health care. Methods This was a cross-sectional survey involving the distribution of self-administered questionnaires among PHC nurses across 47 clinics. Data on socio-demographics, stigma-related mental health knowledge, and nurses' attitudes towards people with mental health problems and mental health care were subjected to descriptive and multiple regression analyses. Results Out of 205 respondents, the majority were female (n = 178, 86.8%). The nurses' median age was 50 (interquartile range: 39-56). Their mean mental health knowledge score was 23.0 (standard deviation [sd]: 3.07) out of 30. Nurses were less knowledgeable about the employment (n = 95, 46.3%), recovery (n = 112, 54.6%), and help-seeking behaviour (n = 119, 58.0%) of people with mental health problems. Professional nurses had a significantly higher mean mental health knowledge score than enrolled/assistant nurses (22.8 vs. 21.1, t 203 = 4.775, p < 0.001). Regarding attitudes, the nurses' mean attitude score was 40.68 (sd: 9.70) out of 96. Two in every five nurses (n = 91, 44.4%) scored above the mean attitude score, implying that they were inclined to have negative (stigmatising) attitudes towards people with mental problems and mental health care. Age (p = 0.048), job category (p < 0.001), and prior in-service mental health training (p = 0.029) made a unique contribution to predicting nurses' attitudes. Conclusion Gaps were established in PHC nurses' stigma-related mental health knowledge. A significant proportion of nurses had a propensity for negative (stigmatising) attitudes towards mental health patients and mental health care. Efforts towards integration of mental health into TB services in this metropolitan and similar settings should address mental health knowledge deficits and factors influencing nurses' negative attitudes. In-service training on mental health should be optimised, with attention to older nurses and enrolled/nursing assistants.